Escenarios de aprendizaje para evaluaciones cortas - Alpizar-Chacon, Isaac (2025)
This article presents an assessment experience in the course “Agile Web Development” of the Information Technology Management program at the Costa Rica Institute of Technology. An educational tool was used to implement short assessments both in-class and at-home. The aim was to analyze how different sequences of activities (scenarios) influence students’ learning, motivation, and participation. By combining quantitative and qualitative data collection, we identified student preferences and potential pedagogical implications for courses in blended learning environments.